REFLECTIONS ON THE IMPLEMENTATION OF THE RULE OF LAW AND DEMOCRACY IN INDONESIA - Muhammad Safaat Gunawan (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2024)
ABSTRACT Reflections on the implementation of the rule of law and democracy in Indonesia reveal challenges and inconsistencies in the application of basic principles of democracy and the supremacy of law. Even though Indonesia has adopted a constitutional democratic system which is supposed to guarantee freedom of opinion, political participation and protection of human rights, reality shows that there is abuse of power and lack of independence of judicial institutions. Political power is concentrated in certain elites, manipulation of the law for the interests of a few parties, and a weak system of checks and balances are issues that undermine the integrity of democracy and the rule of law in Indonesia. The decline in transparency in the political recruitment and election process further worsens public trust in the government and the democratic process itself. Therefore, a strong commitment is needed from all elements of the nation to strengthen and restore the principles of the rule of law and democracy in order to ensure the stability and progress of Indonesia in the future. Keywords: Supremacy of laws; democracy; Abuse of power.